Urban Green Space Policies: Performance and Success Conditions in European Cities - Tüzin Baycan-Levent; Peter Nijkamp (European Regional Science Association (ERSA), 2004)
Urban green spaces play a key role in improving the liveability of our towns and cities. The quality and viability of cities depend largely on the design, management and maintenance of urban green as well as of open and public spaces in order to fulfil their role as an important social constellation and a visual focus. Actually, urban green spaces are seen as an important contribution to a sustainable development of cities. However, the potential of green spaces is not always realized, so that current management practices are sometimes sub-optimal. From a “policy perspective”, the results of several case studies have shown important needs and priorities for the development and management of urban green spaces. It is of strategic importance to compare and evaluate urban green space policies for highlighting the “best practices” for relevant policy recommendations and guidance for society and planning authorities to improve the quality of life in cities. The present study investigates urban green spaces from a policy evaluation perspective and analyses European cities in order to obtain strategic and policy relevant information on the key features of urban green. The study aims to compare and evaluate the current management practices in European cities on the basis of the performance of urban green space policies. The data and information used for comparison and evaluation are based on extensive survey questionnaires filled out by relevant departments or experts of municipalities in European cities that aim to share their experience in innovative green space policies and strategies. A recently developed artificial intelligence method is deployed to assess and identify the most important factors that are responsible for successes and failures of urban green space policies. This approach reveals the most critical policy variables.
Keywords: 330